Impact of frailty on protocol‐based weaning from mechanical ventilation in patients with sepsis: a retrospective cohort study. Issue 1 (30th November 2020) - Matsuda, Wataru; Uemura, Tatsuki; Yamamoto, Makiko; Uemura, Yukari; Kimura, Akio
Abstract : Aim: Frailty has been shown to be associated with prolonged mechanical ventilation (MV). However, due to limited physiological data, it has been unclear how frailty affects weaning from MV in septic patients subjected to a specific weaning protocol. Methods: This was a single‐center retrospective cohort study. The study included patients with sepsis on MV who underwent protocol‐based weaning between August 2015 and December 2018. Frailty was defined as a Clinical Frailty Scale score 4 or more. The association between frailty and weaning was evaluated. Results: Ninety‐nine eligible patients were identified and categorized as frail (n = 67) or not frail (n = 32). The duration of MV was significantly longer in the frail group (8 days versus 5 days, P < 0.01). In multivariate analysis, frailty was independently associated with duration of MV (regression coefficient 17.97, 95% confidence interval 1.77–34.17) and successful weaning (hazard ratio 0.60, 95% confidence interval 0.36–1.00). There was no significant between‐group difference in duration until the first separation attempt or reintubation rate. Respiratory failure was significantly more common in the frail group as a cause of weaning failure, whereas airway failure was common in both groups. Conclusion: Frailty was independently associated with a longer duration of MV in patients with sepsis who underwent protocol‐based weaning. Frail patients were more likely to fail spontaneous breathing trials than nonfrail patients during the weaning process, although the risk after extubation was similar. Abstract : Frailty was associated with delayed extubation on protocol‐based weaning from mechanical ventilation.